Inventory control and intermediation in global supply chains - Zhan Qu; Horst Raff; Nicolas Schmitt (Kiel Institute for the World Economy (IfW), 2015)
The paper develops a simple theoretical model of inventory control in global supply chains. It identifies a role for intermediaries in managing inventory, and shows that inserting an intermediary as an additional link in a supply chain is profitable when demand volatility is high. It also provides conditions under which the intermediary handling inventory is located in the exporting versus the importing country. Trade liberalization in the form of less lumpy trade is shown to expand the role of export and import intermediaries but to have potentially negative effects on the volume of international trade and social welfare in the importing country.
Keywords: F12; F23; L22; 330; international trade; supply chain; inventory; intermediation; lumpy trade